The square root of -15 is 3.87298335
Answer:
Power of a product.
Step-by-step explanation:
Hope this helps!
=)
Lne equals 1 because they cancel each other out. e is the base of ln.
For example: log has a base of 10, log10 = 1
<span>$21 times .06 = $1.26 in taxes and $21 times .15 = $3.15 in tip so you add $21+ 1.26 + 3.15 = $25.41
</span>
The given trinomial can be factored using the factorization method.
x² - 2x - 24
The middle term should be written is such a way that the sum of two terms is equal to the middle one and their product should be equal to the product of first and third term. So the above expression can be written as
= x² -6x + 4x - 24
= x(x-6) + 4(x-6)
= (x-6)(x+4)
Thus, (x-6)(x+4) is the factored form of the polynomial.
So the correct answer is option B